PENGARUH KUALITAS INFORMASI, PERSEPSI RISIKO, PERSEPSI KEAMANAN, DAN PERSEPSI PRIVASI TERHADAP KEPERCAYAAN PENGGUNA E-COMMERCE - Putri, Debby Ananda (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
THE EFFECT OF QUALITY INFORMATION, PERCEPTION OF RISK, SECURITY PERCEPTION AND PRIVACY PERCEPTION ON THE TRUST OF E- COMMERCE USERS, The purpose of this study is to examine the factors affecting the confidence of e-commerce users. This research is conducted at the Faculty of Economics and Business, University of Brawijaya using a survey method. The research uses samples of respondents as much as 292 students of Accounting Department who use e-commerce system. The research results indicate that the construct of quality information and privacy perceptions positively influence the confidence of e-commerce users. However, the construct of risk perception and the perception of security has no effect on the confidence of e-commerce users. It means that the confidence of e-commerce users is influenced by the quality of information and the perception of privacy. Hence, management and system developers should pay attention on the quality of information and the perception of privacy in order to improve the trust of e- commerce users.Keywords: Quality of information, risk perception, perception of security, trust, e- commerce.